William Russell correspondence - Russell, William, active 1865.
ALS (1865 April 19; Head Quarters Cavalry, Middle Military Division) from Russell to Gen. George H. Chapman ordering him to investigate the treasonous attitude of a group of women who expressed joy at Abraham Lincoln's assassination.
Union Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Chapman, George H., -- 1832-1882 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Treason -- United States; Army officers